EFFECT OF DIETARY CHOLINE ON THE PRODUCTION PERFORMANCE AND CARCASS CHARACTERISTICS OF COBB 500 CHICKENS: Performance Evaluation of Cobb 500 Broiler Strain Fed on Dietary Supplementation of Choline - Sokunbi, Abimbola Elizabeth; Sogunle, Olajide Mark; Abiona, John Adesanya; Owolabi, Ayobami John; Ogunsola, Oluwatobi Michael; Yusuf, Azeez Olanrewaju (Polish Journal of Natural Sciences, 2024)
Choline serves a number of crucial metabolic functions, making it an essential component in poultry diets which include; lipid transport, cell signalling, and biosynthesis of methylated compounds. The objective of this study was to evaluate the performance and carcass characteristics of Cobb 500 broiler strain fed on dietary supplementation of choline. One hundred and forty-four (144) day old unsexed Cobb 500 broiler chickens were randomly assigned to three treatment groups with four (4) replications of twelve (12) chicks each in a Completely Randomized Design. Three levels of choline (0, 1200, 1400 ppm/100 kg of feed) were supplemented in the chick’s feed at starter phase (0-21days), while at finisher phase (21-49 days) three levels of choline (0, 800, 1000 ppm/100 kg feed) were also supplemented in the chicken’s feed. Results showed that different levels of choline had no significant effect (P>0.05) on the body changes of broiler chickens at starter and finisher phases. However, feed conversion ratio was best (P<0.05) for chicks supplemented with 1200 ppm at starter phase compare to the finisher phase. At finisher phase, feed intake (3216.93 g/bird) of broiler chickens offered 800 ppm choline were significantly (P<0.05) reduced when compared to control diets (3380.11 g/bird). Dressing percentage significantly (P<0.05) increased at 800 ppm while the thigh decreased (P<0.05) with choline increment. In conclusion, choline supplementation in the diets of broiler chickens at 1200 and 800 ppm/100 kg feed improved the growth performance and carcass characteristics of Cobb 500 broiler strain chickens at starter and finisher phases respectively.